2021
DOI: 10.31486/toj.20.0086
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Manifestations of COVID-19: A Review of What We Know

Abstract: Background: The coronavirus disease 2019 (COVID-19) is not just a disease of the respiratory system. The virus can affect the gastrointestinal (GI) tract as well. Recognizing the various manifestations in every organ system is important because these manifestations can contribute to community-based transmission. Methods: We outline the evidence of the pathophysiology of COVID-19 in the GI tract, the effects of the virus on the gut and liver, the presence of the virus in stool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 42 publications
2
46
1
3
Order By: Relevance
“…Related to COVID-19 infection, SARS-CoV-2 affects the gastrointestinal tract as evidenced by gastrointestinal symptoms and detection of the virus in faeces ( Groff et al., 2021 ). Additionally, viral antigens have been found in intestinal enterocytes after resolution of clinical illness in adults ( Gaebler et al., 2021 ) and zonulin hyper permeability of the mucosal barrier coincides with SARS-CoV-2 antigenemia ( Yonker et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Related to COVID-19 infection, SARS-CoV-2 affects the gastrointestinal tract as evidenced by gastrointestinal symptoms and detection of the virus in faeces ( Groff et al., 2021 ). Additionally, viral antigens have been found in intestinal enterocytes after resolution of clinical illness in adults ( Gaebler et al., 2021 ) and zonulin hyper permeability of the mucosal barrier coincides with SARS-CoV-2 antigenemia ( Yonker et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…With both respiratory and gastrointestinal symptoms being quite common in the context of Covid-19 ( Cares-Marambio et al, 2021 ; Groff et al, 2021 ) and ACE2 being highly expressed in the alveolar epithelial type II cells and the intestinal endothelial cells ( Williams et al, 2021 ), some researchers have suggested the potential of SARS-CoV-2 entry through the intestine ( Lehmann et al, 2021 ; Mönkemüller, Fry, & Rickes, 2020 ; Zhang et al, 2020 ). RNA of the SARS-CoV-2 has been identified in stool samples and rectal swabs, even in cases with negative nasopharyngeal swabs ( Tang, Schmitz, Persing, & Stratton, 2020 ).…”
Section: Peripheral Pathways That May Contribute To Neuroinflammationmentioning
confidence: 99%
“…Additionally, ACE2 receptors in the gastrointestinal tract play a crucial regulatory role in homeostasis, gut microbiome, and innate immunity. As a result, binding SARS-CoV-2 to these receptors and activating other epithelial surface proteins that can facilitate the entry of the virus may be one of the reasons for coronavirus infection in gastrointestinal tissues 35 . Conversely, live virus and RNA material that have been detected in the stools of COVID-19 patients were reported play a role in SARS-CoV-2 entry into cells starting from the apical surface and activating epithelial cell fusion in the intestine 36 38 .…”
Section: Introductionmentioning
confidence: 99%